If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -6 = 8x Reorder the terms: -6 + 5x = 8x Solving -6 + 5x = 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -6 + 5x + -8x = 8x + -8x Combine like terms: 5x + -8x = -3x -6 + -3x = 8x + -8x Combine like terms: 8x + -8x = 0 -6 + -3x = 0 Add '6' to each side of the equation. -6 + 6 + -3x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -3x = 0 + 6 -3x = 0 + 6 Combine like terms: 0 + 6 = 6 -3x = 6 Divide each side by '-3'. x = -2 Simplifying x = -2
| v-1/2 | | 12(1+6d)=expand | | 8x+3=70 | | (x^2)=38 | | 5(n+2)-3=22 | | x^2+27x+28= | | 2/7x+1/2x=3/5x+1 | | 24x-8-13x+2=24x-6-13x+11 | | 1=4x-5x+8 | | -4x-9-x=-9 | | 7(y-4)-7= | | 6-5x=8x | | y/6+22=2y | | 4^3(8^1/3z^2) | | C=12m+(4m-10) | | -23+x=x+11 | | -7(3q-1)=expand | | 5x+76x=105 | | 2y+4+3y-5+y=29 | | 0.88*x=22 | | z^2+12=48 | | log(128)4=x | | (3x)^2/3=0 | | 18-x/3=16 | | (x^2)=80 | | (3x-2)^2/3=16 | | -(4/7)-(1/5) | | x+2/13=9/13 | | (x^2)=-45 | | 2w^3-32w^2+6w-16= | | -4-7V=-26/3 | | 6.27=y/2.5-9.8 |